Proposta metodológica para avaliar governança da água em nível de bacias hidrográficas na Colômbia: estudo de caso da bacia hidrográfica do Rio Tillavá - departamento do Meta - Albarracín, Astrid Guerrero (2017)
Although there are policies, norms and instruments that guide water management at the basin level in Colombia, there is still no clear understanding of the processes that are involved in the Colombia’s water governance development, for example, the role of different actors in river basins protection. The present research intends to emphasize the importance of evaluating water governance processes at the river basin level, and proposes a system of indicators that will serve as a decision-making tool for regional and national environmental authorities, related to water resources Management. The methodology adopted in the present work involved four stages: a bibliographic search that made possible to understand relevant topics on water governance evaluation process; The proposed indicators selection was subsidized by the dimensions and principles set out by the Organisation for Economic Co-operation and Development (OECD) for water governance; then comes the indicators system validation in two stages: First, the indicators system was submitted to criticism by experts using the Delfi method, in which, all indicators were weighted and hierarchized according to their degree of importance. Finally, a case study was carried out in the Tillava River’s basin in the department of Meta, Colombia. Questionnaires were applied to obtain the necessary information to feed the proposed indicators system; the target are actors that are part of the basin, whose were divided into two categories: residents and managers, aiming to obtain both perspectives on basin’s water governance separately. According to collected data analysis, it can be concluded that the views of the residents and managers of hydrografic basin are very similar; both groups consider that there is a water governance in the basin, even though its level still does not allow the compliance of all OECD principles on which water governance is based on.